Reality & Epic Literature; The Scientificity Behind The Hervör Saga - Mario; Ruiz Magdonel, Miguel Ángel (Cinzontle, 2021)
Fantastic literature implies a proccess of transformation of everyday life. It has great value today due to its popularity among young people and cinema; he has also influenced the creation of works such as The Lord of the Rings and The Hobbit. The objective of this research is to analize, from the point of view of scientificity, fantastic aspects within the Saga of Hervör. This will allow us to analize from a rational perspective what the autor supports.